1992
DOI: 10.2307/1389300
|View full text |Cite
|
Sign up to set email alerts
|

Injury and Depression: The Mediating Effects of Self-Concept

Abstract: This study further specifies the relationship between injury, self-conceptions, and depression. With the use of path analysis, we look at the direct and indirect effects of pain and work limitation associated with a job-related injury on self-efficacy, self-esteem and depression for a sample of injured workers (N = 1,037). As expected, we found that self-efficacy and self-esteem are negatively associated with depression, while work limitation and pain are positively associated with depression. We also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
2
5
0
1
Order By: Relevance
“…The results suggests that individuals with a high level of work self-efficacy, also presented with a high level of coping with pain self-efficacy, a high level of physical function selfefficacy, a high level of coping with symptoms self-efficacy, and that they were more likely to return to work following injury. These conclusions are consistent with the results of Seff, Gecas, & Ray (1992) who reported a significant correlation between high self-efficacy and self-esteem. Similarly, Lackner, Carosell, & Feuerstein (1996) concluded that participants with higher levels of physical function self-efficacy eve ~e significantly greater physical function self-efficacy than participants with lower levels of physical function self-efficacy.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results suggests that individuals with a high level of work self-efficacy, also presented with a high level of coping with pain self-efficacy, a high level of physical function selfefficacy, a high level of coping with symptoms self-efficacy, and that they were more likely to return to work following injury. These conclusions are consistent with the results of Seff, Gecas, & Ray (1992) who reported a significant correlation between high self-efficacy and self-esteem. Similarly, Lackner, Carosell, & Feuerstein (1996) concluded that participants with higher levels of physical function self-efficacy eve ~e significantly greater physical function self-efficacy than participants with lower levels of physical function self-efficacy.…”
Section: Resultssupporting
confidence: 92%
“…These results were supported by Seff, Gecas, and Ray (1992) who reported a significant correlation between high self-efficacy and self-esteem; both were negatively related to depression. Likewise, Lackner, Carosell, and Feuerstein (1996) concluded that participants with higher levels of physical function self-efficacy revealed significantly greater physical function than participants with lower physical function selfefficacy.…”
Section: Self-efficacy and Impairmentsupporting
confidence: 55%
See 1 more Smart Citation
“…Self-esteem refers to an individual's feelings of moral value or worth, or to the extent to which people hold themselves in high or low regard (Seff et al 1992). It was measured by two items: 'In general, I feel very positive about myself', adopted from the self-acceptance scale (reversed scores; Ryff and Singer 1998), and 'At times I feel as if I am a failure', adopted from the Rosenberg (1965) self-esteem scale.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Competence refers to an individual's sense of effectiveness, mastery, or self-efficacy in dealing with the environment, that is, the ability or the skill one has to accomplish tasks (Seff et al 1992) Similarly, autonomy refers to feelings of achievement and control, with the absence of physical barriers and power relations (McBride et al 2005). It was measured by the item 'I feel free to decide how to live my life', adopted from Ryan and Deci's (2001) autonomy scale, with a range of 1 (agree strongly) to 5 (disagree strongly).…”
Section: Dependent Variablesmentioning
confidence: 99%